2013
DOI: 10.2355/isijinternational.53.1779
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of BF Hearth Protection Using Spinel Formation by Slag Composition Control

Abstract: The formation of titanium carbonitride has been used as a conventional method to protect the refractory wear in the hearth. Because titanium carbonitride is formed only in the molten iron, the area that can form a protective layer in the hearth is limited. There is another possibility to protect the refractory wear by introducing the compounds with high melting point in the slags. If the compounds with high melting point are simultaneously formed in the molten iron and slag by adding TiO2, it might be more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…The heat capacity and enthalpy change of the slag reflected the temperature resistance to the fluctuation of the slag under a specific heat input, which can be defined here as thermal stability. The heat capacity and enthalpy change of the slag can be estimated according to formulas [1] through [9] due to the crystal transformation heat, phase transformation heat, and chemical reaction heat in the slag during the melting processes. We used a FactSage computer package to conduct accurate thermodynamic calculations in this study.…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The heat capacity and enthalpy change of the slag reflected the temperature resistance to the fluctuation of the slag under a specific heat input, which can be defined here as thermal stability. The heat capacity and enthalpy change of the slag can be estimated according to formulas [1] through [9] due to the crystal transformation heat, phase transformation heat, and chemical reaction heat in the slag during the melting processes. We used a FactSage computer package to conduct accurate thermodynamic calculations in this study.…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%
“…Feng et al 8) investigated the effect of TiO 2 on the phase compositions of titanium-bearing slag by Fourier transform infrared spectroscopy (FTIR), showed that the polymerization degree in the slag decreased and the content of perovskite phase in the slag increases with the increase of TiO 2 content. Although the influence of TiO 2 and basicity on the viscosity of slag has been widely researched, 9) much less attention has been paid to ultra-high titanium slag from the perspective of heat input.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, raw materials containing titania charged in BF is an effective measure to protect the hearth at the end of the service. [15][16][17][18] The titania in iron ore is reduced to form titanium and the titanium is dissolved into molten…”
Section: Introductionmentioning
confidence: 99%
“…It is the concern for operators to choose the economical ore containing titania for protection. [10][11][12] The effect of titania content on metallurgical properties of the ore was investigated by many papers, 13,14) the evaluation of the economy only based on price was concluded to be one-sided, few people synthetically evaluate the economy of the ore containing titania based on the price, the flux amount, the iron production and the slag amount. 15) In addition, the evaluation index of the protection effect is lacking, the stability of the protection effect can't be guaranteed due to the change of operation, the time to increase titanium load becomes the key for operators.…”
Section: Introductionmentioning
confidence: 99%